Pengaruh Pendidikan Terhadap Prestasi Kerja Pegawai Aparat Desa Di Kantor Pemerintahan Desa Kencong Wilayah Kecamatan Kencong Kabupaten Jember - Lukman Hakim; Totok Mardianto (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2019)
The problem that is background research this is in the doing his duty employee village officials often a rather slow and less mean it , that a thus not immediately straightened out will or could harm agency , where is village officials that is on duty and finally can harm a country . A aim research this a 1) The test in a manner empirical influence education village officials in office government village Kencong sub district area Kencong districts Jember. 2) The test in manner empirical influence in a manner partial education village officials in office government village officials in office government village Kencong subdistrict area Kencong districts Jember . 3) A analyzeÂ  influence education village officials in office government village officials in office government village Kencong subdistrict area Kencong districts Jember.